Establishing (Un)Certainty: Language and Reproducing Suspicion in Forensic Medical Evaluations - Chan, Andrew (Refuge, 2026)
While forensic medical evaluations (FMEs) have been shown to bolster rates of asylum approval in the United States, a discourse analysis of deidentified FMEs reveals a more nuanced function. In the suspicious and disbelieving culture of asylum adjudication, the rhetorical strategies and devices along with mandated neutral language in FMEs can inadvertently marginalize, reproduce suspicion of, and introduce (un)certainty about applicant testimony. Thus, FMEs can be co-opted to become a technology of state control over asylum seeker’s lives by allowing adjudicators to utilize them as flexible justification to support arbitrary asylum decisions under the guise of medical evidence.